Associations Between Two Polymorphisms in the Methylenetetrahydrofolate Reductase Gene and Placental Abruption - Ananth, Cande V. (2007)
OBJECTIVE: Heritable thrombophilias have been implicated as a potential etiology of abruption via vascular disruption at the uteroplacental interface. Polymorphisms of the methylenetetrahydrofolate reductase (MTHFR) gene have been linked to vascular complications outside of pregnancy, including stroke. Given the underlying thrombotic nature of abruption, we hypothesized that polymorphisms in the MTHFR gene are associated with abruption. STUDY DESIGN: We examined 2 variants in MTHFR: 677C→T and 1298A→C in genomic DNA extracted from maternal blood from the New Jersey-Placental Abruption Study, an ongoing, multicenter case-control study. We identified 195 women with a clinical diagnosis of abruption (cases), and 189 controls matched on race/ethnicity and parity. We assessed allele and genotype frequencies, and their associations with abruption risk after adjusting for confounders through multivariable logistic regression analysis. RESULTS: The wild-type allele (C) frequency of the 677C→T variant of MTHFR among cases and controls was 69.0% and 64.3%, respectively, and the wild-type allele (A) of the 1298A→C variant was 75.9% and 79.4%, respectively. Distributions of the 677C→T alleles among controls violated the Hardy-Weinberg equilibrium (P=0.007), while those of the 1298A→C alleles were in equilibrium (P=0.825). In comparison to the wild-type genotype (C/C), the homozygous mutant form (T/T) of 677C→T was not associated with abruption (OR 0.60, 95% confidence interval (CI) 0.33, 1.18). Similarly, the homozygous mutant form (C/C) of the 1298A→C polymorphism was equally distributed between cases and controls (OR 2.28, 95% CI 0.82, 6.35). Plasma homocysteine and vitamin B(12), but not folate, concentrations were elevated in cases compared to controls among women with the wild-type genotype of MTHFR 677C→T (P=0.039 for homocysteine; P=0.048 for B(12) and P=0.224 for folate, respectively). CONCLUSIONS: In this population, neither heterozygosity nor homozygosity for the 677C→T and 1298A→C variants in MTHFR was associated with placental abruption.